Cytotoxic Effect of Biogenic Selenium Nanoparticles Using Bacteriocin of Acinetobacter baumannii Isolated from Burns and Wound Infections - Salman, Maryam Faysal; Al-Mudallal, Nada H. A. L.; Ahmed, Mais Emad (Iraqi Journal of Science, 2025)
Recently, advancements in nanotechnology have opened up new avenues for enhancing healthcare outcomes by leveraging the unique properties of nanomaterial. Scientists have previously developed complexes of bacteriocins with nanomaterials or bacteriocin-nanoconjugates for diverse biomedical applications that utilize bacteriocins. The usage of bacteriocin–nanoconjugates has several benefits, including enhanced stability over extended use, defense against proteolytic enzyme degradation, and synergistic efficacy. The requirement to provide new antibiotic alternatives is becoming more pressing in this regard. Because of their special qualities, metal oxide nanomaterials are currently attracting a lot of attention as possible antimicrobial and anti-cancer agents. The bacteriocin-like inhibitory substance (BLIS) from Acinetobacter bumannii used to synthesiss selenium nanoparticles. Atomic Force Microscopy (AFM), Field Emission Scanning Electron Microscope (FESEM), X-Ray Diffraction (XDR) analysis and UV visible spectrometry were used to characterize the biosynthesized nanoparticles and ascertain the product's chemical and physical properties XRD verified the hexagonal structure, AFM analysis used to reveal the roughness and distribution of nanoparticles indicated the size range at 81,23 nm, and FESEM validated the surface morphology. The UV-visible spectroscopic analysis revealed that the synthesized nanoparticles exhibited their highest absorption peaks at a wavelength of 270 nm.  Minimum inhibitory concentration (MIC) at 250 mg/ml Biogenic selenium nanoparticles demonstrated comparable in order to ascertain the optimal antimicrobial activity against pathogenic microorganisms through the use of a well diffusion method, pathogenic microorganisms were isolated clinically infections in Iraqi patients and identified using the VITEK-2 Compact. The cytotoxicity assays demonstrated that the treatment with biologically synthesized selenium nanoparticles did not markedly compromise the viability of human lymphocytes.